2011
DOI: 10.1152/ajprenal.00249.2010
|View full text |Cite
|
Sign up to set email alerts
|

Midkine, a heparin-binding protein, is increased in the diabetic mouse kidney postmenopause

Abstract: Diamond-Stanic MK, Romero-Aleshire MJ, Hoyer PB, Greer K, Hoying JB, Brooks HL. Midkine, a heparin-binding protein, is increased in the diabetic mouse kidney postmenopause. Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Persistent hyperglycaemia is known to induce severe endothelial dysfunction, oxidative stress and inflammation, leading to changes in renal morphology and haemodynamics. These processes involve various chemokines, including Ang II, NO, TGF‐β, IL‐1β, plasminogen activator inhibitor‐1 (PAI‐1) and MCP‐1 (Diamond‐Stanic et al ., ). Diabetic nephropathy thus warrants a multidisciplinary approach to elucidate the underlying molecular mechanisms.…”
Section: Mk and Diabetic Nephropathymentioning
confidence: 97%
See 2 more Smart Citations
“…Persistent hyperglycaemia is known to induce severe endothelial dysfunction, oxidative stress and inflammation, leading to changes in renal morphology and haemodynamics. These processes involve various chemokines, including Ang II, NO, TGF‐β, IL‐1β, plasminogen activator inhibitor‐1 (PAI‐1) and MCP‐1 (Diamond‐Stanic et al ., ). Diabetic nephropathy thus warrants a multidisciplinary approach to elucidate the underlying molecular mechanisms.…”
Section: Mk and Diabetic Nephropathymentioning
confidence: 97%
“…Macrophage recruitment activated by MK in TECs through MCP‐1 induction at the early stage of diabetic nephropathy eventually results in tubulointerstitial injury (Kosugi et al ., ). In addition, menopause aggravates diabetic nephropathy and MK is up‐regulated (demonstrated using DNA microarrays; Diamond‐Stanic et al ., ). Endothelial NO synthase expression is strikingly decreased in this model (Figure ).…”
Section: Mk and Diabetic Nephropathymentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence of kidney disease in women is lower than in men in the same age group, and the loss of ovarian hormones is thought to accelerate kidney damage. The VCD model of menopause has been used to examine the impact of menopause on the onset and progression of diabetic kidney disease and the metabolic syndrome (4,9). First, to examine the impact of menopause on the progression of diabetic kidney disease, we used streptozotocin (STZ) (model of Type 1 diabetes, hyperglycemia) to induce diabetes in VCD-treated animals during perimenopause or 2 wk after the onset of menopause.…”
Section: Postmenopausal Diabetic Kidney Disease and The Metabolic Synmentioning
confidence: 99%
“…We also found a fracture-induced increase in Mdk serum levels, which was attenuated by the Mdk-Ab. Because it was shown previously that Mdk is an estrogen-responsive gene and that Mdk expression is enhanced in the murine postmenopausal diabetic kidney [ 17 ], we hypothesized that Mdk may also be involved in the pathogenesis of compromised bone healing after estrogen withdrawal. The present study demonstrated that Mdk serum levels were significantly increased after fracture, particularly in osteoporotic mice, and that treatment with an Mdk-Ab abolished the negative influence of ovariectomy (OVX) on bone healing.…”
Section: Introductionmentioning
confidence: 99%